Family function, coping style and well-being affect job burnout among telecommunication employees: a cross-sectional study in China - Song, Jingjing; Xu, Xinqing; Zhang, Hanzhong; Pan, Zhenyu; Zhu, Jinghua; Shao, Jiangang; Jia, Liping (Frontiers in Public Health, 2025)
BackgroundThe rapid development of the digital economy has raised higher work demands for telecommunication employees, resulting in a growing prevalence of job burnout in this sector. Therefore, exploring the causes of job burnout among telecommunication employees and offering corresponding recommendations holds significant practical implications.MethodsEmploying a stratified random sampling method, we surveyed 10,397 telecommunication employees from Shandong Province, China, achieving 8,018 valid responses (response rate: 77.1%). Using personal information forms and four scales. The collected data were processed and analyzed using SPSS 26.0.ResultsUsing partial correlation analysis, significant correlations (ps < 0.001) were found among family function, coping style, well-being, and job burnout. Coping style and well-being were identified as mediators between family function and job burnout, explaining 33.11% (indirect effect size = −0.101), and 24.59% (indirect effect size = −0.075) of the total effects, respectively. In addition, coping style and well-being play a chain mediating role between family function and job burnout, contributing 14.10% (indirect effect size = −0.043) to the total effects.ConclusionThis study highlights that family function not only directly impacts job burnout in telecommunication employees but also exerts an indirect influence through the chain mediating effect of coping style and well-being. Since this study employs a cross-sectional design, it can only reveal the correlations between these variables. Future research should focus on conducting longitudinal studies to further explore the causal relationships among the variables. The results of this study have important guiding significance for enterprises to pay attention to the family function of employees, cultivate positive coping style, improve their well-being, and reduce the level of job burnout of employees.